Adhesive, insulating adhesive film for busbar and preparation method of insulating adhesive film
By using new adhesives with components such as saturated polyester resin, tackifying resin, flame retardant filler, reactive isocyanate and sealed isocyanate in the insulating film for busbars, the problems of high and long heat pressing temperature in the prior art are solved, and the film with fast low-temperature hot pressing and high aging resistance are achieved.
Patent Information
- Application Number
- CN202411922017.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-11
AI Technical Summary
The existing insulating film for busbars requires high temperature and long time during the hot pressing process, resulting in low production efficiency, high cost, and insufficient aging resistance.
Adhesives with low temperature flowability and high aging properties are prepared by optimizing the proportion and type of these components by using a new type of adhesive, including saturated polyester resin, tackifying resin, flame retardant filler, reactive isocyanate and blocking isocyanate.
It realizes hot press bonding at low temperature and in a short time, improves production efficiency and aging resistance of the adhesive film, and ensures the safety and reliability of the busbar.
Smart Images

Figure CN119592287A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of insulating adhesive films, and in particular relates to an adhesive, an insulating adhesive film for a busbar and a preparation method thereof. Background Art
[0002] The busbar is a single-layer or laminated connection bar, which is made of insulating film and copper bars laminated by hot pressing. It makes the connection between components or sub-modules into a flat cross-section. Opposite currents pass through adjacent copper bars, and the magnetic fields they generate can cancel each other out, making the parasitic inductance in the busbar smaller. The insulating film on the surface and middle of the busbar, which has bonding and insulating effects, is particularly important for the safety and reliability of the busbar. At present, the adhesives for insulating films for busbars mainly include epoxy adhesives and saturated polyester adhesives. The bonding performance and aging resistance of epoxy adhesives are very excellent, but they have disadvantages such as high storage requirements, high hot pressing temperature, and long hot pressing time. In order to ensure its aging resistance, the hot pressing time of saturated polyester adhesives is more than 15 minutes.
[0003] In order to improve the efficiency of busbar production, reduce the hot pressing temperature, and reduce the hot pressing time, low melting point resins are usually mixed or low molecular weight compatibilizers are used to improve the fluidity of adhesives at high temperatures. For example, invention patent CN104178044A discloses a saturated polyester resin adhesive, which uses a saturated polyester resin A with a low glass transition temperature and a saturated polyester resin B with a high glass transition temperature to blend to reduce the softening point of the adhesive layer, but the polyester resin with a low glass transition temperature will increase the initial adhesion of the adhesive layer, which is not convenient for moving and positioning during lamination hot pressing. For example, inventions CN 106675003 A and CN 106700509 A disclose a copolyamide resin modified saturated polyester resin adhesive, and a low molecular weight compatibilizer is added to enable the adhesive layer to be hot pressed at low temperature. However, the copolyamide resin has a high acid value, which makes the saturated polyester resin adhesive easy to be esterified, so the resistance to cold and hot shock and high temperature aging is poor.
[0004] Therefore, how to lower the hot pressing temperature and shorten the hot pressing time while maintaining the aging resistance of the insulating film for busbars is one of the problems that the insulating film industry needs to solve urgently. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides an adhesive, an insulating film for busbar and a preparation method thereof, which can meet the requirements of long-term high-temperature and high-humidity aging, hot and cold shock aging and thermal oxygen aging, and has a low pressing temperature and a short pressing time. The insulating film has stable performance and high production efficiency.
[0006] The first object of the present invention is to provide an adhesive, which comprises, by weight, 40-90 parts of a saturated polyester resin, 10-40 parts of a tackifying resin, 30-80 parts of a flame retardant filler, 3-10 parts of a curing agent, 0.1-0.5 parts of a curing accelerator and 50-300 parts of an organic solvent; the tackifying resin has a softening point of 40°C-120°C. If the softening point is lower than 40°C, the adhesive layer will have initial adhesion at room temperature, which is not convenient for positioning before hot pressing; if the softening point is higher than 120°C, the fluidity of the adhesive layer is poor, and the adhesion of low-temperature hot pressing is poor; the curing agent comprises a reactive isocyanate and a blocked isocyanate; The unsealing temperature of the blocked isocyanate is 70°C-120°C. If the unsealing temperature is lower than 70°C, the adhesive may be unsealed during the drying process after coating, which affects the bonding strength of the adhesive. If the unsealing temperature is higher than 120°C, low-temperature hot pressing cannot unblock the blocked isocyanate, which affects the aging performance of the adhesive. The mass ratio of the reactive isocyanate to the blocked isocyanate is 1:(1-5). When the mass ratio is greater than 1:1, the pre-crosslinking degree of the adhesive layer is too high, and the fluidity is poor during hot pressing, and excellent bonding strength cannot be obtained. When the mass ratio is less than 1:5, the crosslinking degree of the adhesive layer is too low, and the fluidity is too high during hot pressing, which may cause overflow.
[0007] Furthermore, the weight parts of the saturated polyester resin can be 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts, 90 parts, etc.;
[0008] The weight parts of the tackifying resin can be 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, etc.;
[0009] The weight proportion of the flame retardant filler can be 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, etc.;
[0010] The weight parts of the curing agent can be 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, etc.;
[0011] The weight portion of the curing accelerator can be 0.1 part, 0.15 part, 0.2 part, 0.25 part, 0.3 part, 0.35 part, 0.4 part, 0.45 part, 0.5 part, etc.;
[0012] The weight parts of the organic solvent can be 50 parts, 100 parts, 150 parts, 200 parts, 250 parts, 300 parts, etc.
[0013] In one embodiment of the present invention, the reactive isocyanate is selected from one or more of diisocyanate and its dimer, trimer and biuret polyisocyanate.
[0014] Furthermore, the diisocyanate is selected from one or more of toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI) and the like.
[0015] In one embodiment of the present invention, the blocked isocyanate is obtained by reacting a blocking agent with the reactive isocyanate; the molar ratio of active hydrogen in the blocking agent to isocyanate in the reactive isocyanate is (1-1.5):1; when the molar ratio of active hydrogen to isocyanate is less than 1:1, the isocyanate cannot be completely blocked, resulting in poor storage properties of the blocked curing agent; when the molar ratio of active hydrogen to isocyanate is greater than 1.5:1, there is almost no effect on the isocyanate blocking rate, and the cost is relatively high.
[0016] Furthermore, the molar ratio of active hydrogen in the blocking agent to isocyanate in the reactive isocyanate is (1:1), (1.1:1), (1.2:1), (1.3:1), (1.4:1), (1.5:1), etc.
[0017] In one embodiment of the present invention, the blocking agent is selected from one or more of methyl tert-butyl ketone oxime, diisopropyl ketone oxime, 3,5-dimethylpyrazole, 2-methylimidazole and 1,2,4-triazole;
[0018] The reaction temperature is 20°C-100°C, and the reaction time is 0.5h-6h.
[0019] In one embodiment of the present invention, the number average molecular weight of the saturated polyester resin is 3000-40000. When the number average molecular weight is lower than 3000, the temperature resistance is poor, and the adhesive has initial adhesion which is not conducive to processing; when it is higher than 40000, the viscosity of the adhesive solution is too high which is not conducive to coating; the glass transition temperature is -20°C to 80°C. When the glass transition temperature is lower than -20°C, the adhesive has initial adhesion which is not conducive to processing; when it is higher than 80°C, the adhesive layer is hard and the busbar is bent. Cracking and debonding problems may occur during the processing; the hydroxyl value is 8mgKOH / g-20mgKOH / g. When the hydroxyl value is lower than 8mgKOH / g, the adhesive has a low crosslinking degree and poor temperature resistance; when it is higher than 20mgKOH / g, the adhesive has a high crosslinking degree, which will cause the adhesive layer to be harder; the acid value is not greater than 3mgKOH / g. If the acid value is greater than 3mgKOH / g, the carboxyl group will cause the degree of ester exchange to increase, and the adhesive layer will not be resistant to hydrolysis, that is, it will not be resistant to high temperature and high humidity aging.
[0020] Furthermore, the saturated polyester resin is selected from one or more of ES380, ES403, ES510, ES600 and EW960 of SK Chemical of South Korea, and Vylon226, 240, 560, 660 and 885 of Toyobo.
[0021] In one embodiment of the present invention, the tackifying resin is selected from one or more of rosin resin, epoxy resin, terpene resin, phenolic resin and petroleum resin;
[0022] The flame retardant filler is selected from one or more of phosphorus flame retardants, nitrogen flame retardants and metal hydroxides;
[0023] The curing accelerator is selected from organotin accelerators;
[0024] The organic solvent is selected from one or more of butanone, acetone, cyclohexanone, ethyl acetate and butyl acetate.
[0025] Further, the tackifying resin is selected from one or more of rosin resins GA85A, GA90A, GA95, GA105, GB110 and GB120 of Arakawa Chemical, epoxy resins NPES901, NPES902, NPES903, NPES903H, NPES904 and NPES904H of Nan Ya Plastics, and phenolic resins SH2095, SH2107, SH2100 and SH2116 of Jinan Shengquan.
[0026] The phosphorus-based flame retardant is selected from one or more of diethyl aluminum hypophosphite, ammonium polyphosphate and aluminum hypophosphite; the nitrogen-based flame retardant is selected from melamine and / or melamine cyanurate; and the metal hydroxide is selected from aluminum hydroxide and / or magnesium hydroxide.
[0027] The second object of the present invention is to provide a method for preparing the adhesive, comprising the following steps: saturated polyester resin, tackifying resin, flame retardant filler, curing agent and curing accelerator are uniformly dispersed in an organic solvent to obtain the adhesive.
[0028] The third object of the present invention is to provide an insulating adhesive film for a busbar, wherein the insulating adhesive film for a busbar comprises an insulating film layer and an adhesive layer arranged on the insulating film layer; the adhesive layer is prepared from the adhesive.
[0029] In one embodiment of the present invention, the insulating film layer is selected from a polyethylene terephthalate film layer, a polybutylene terephthalate film layer, a polyethylene naphthalate film layer, a polyimide film layer, a polycarbonate film layer, an aromatic polyamide film layer, a polyphenylene sulfide film layer or a polyphenylene ether film layer.
[0030] In one embodiment of the present invention, the thickness of the insulating film layer is 50 μm-300 μm; the thickness of the adhesive layer is 10 μm-50 μm.
[0031] In one embodiment of the present invention, the preparation of the insulating adhesive film for the busbar specifically includes the following steps: coating an adhesive on the insulating film layer, and obtaining the insulating adhesive film for the busbar through drying and pre-curing.
[0032] The technical solution of the present invention has the following advantages over the prior art:
[0033] (1) The adhesive of the present invention uses saturated polyester resin as the main resin and adds a tackifying resin to obtain an adhesive layer with a low softening point; further, a reactive isocyanate and a blocked isocyanate are added to obtain an adhesive capable of reacting at low temperature.
[0034] (2) The adhesive of the present invention has excellent low-temperature fluidity and low-temperature reactivity. As a hot melt adhesive layer or a semi-cured adhesive layer, it can be hot pressed at a low temperature of 120°C-140°C and a short time of 240s-600s, and has good bonding strength to pure copper and its plated parts; and there is no initial adhesion at room temperature, and it can be positioned on the busbar.
[0035] (3) The adhesive described in the present invention is used for insulation on the busbar surface or between laminates, has excellent high and low temperature bonding strength, long-term high temperature and high humidity aging resistance, heat shock aging resistance, thermal oxygen aging resistance, and is easy to implement. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:
[0037] Figure 1 It is a schematic structural diagram of the insulating adhesive film for busbar of the present invention;
[0038] Explanation of the reference numerals: 1 - insulating film layer, 2 - adhesive layer. DETAILED DESCRIPTION
[0039] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. It should be understood that the specific embodiments are only used to explain the present invention, but the embodiments are not intended to limit the present invention.
[0040] In the present invention, unless otherwise explained, technical and scientific terms used in the present invention have the same meanings as commonly understood by those skilled in the art to which the present invention belongs.
[0041] In the present invention, unless otherwise stated, the term "and / or" used in the present invention includes any and all combinations of one or more of the associated listed items.
[0042] In the present invention, unless otherwise stated, the experimental methods used in the embodiments of the present invention are conventional methods unless otherwise stated, and the materials, reagents, etc. used are all commercially available unless otherwise stated.
[0043] In the present invention, unless otherwise stated, when the terms "comprise" and / or "include" are used in the specification of the present invention, it indicates the existence of the described features, integers, steps, operations, raw materials or components, but does not exclude the existence or addition of one or more other features, integers, steps, operations, raw materials, components or their combinations.
[0044] In the present invention, unless otherwise specified, the preparation of the blocked curing agent used in the embodiments of the present invention specifically includes the following steps: weighing the blocking agent and the reactive isocyanate so that the molar ratio of the active hydrogen in the blocking agent to the isocyanate in the reactive isocyanate is 1.1:1; slowly dropping the pre-configured blocking agent solution into the reactive isocyanate solution, heating to 70°C after the dropping is completed and keeping the temperature for reaction for 4 hours to obtain the blocked isocyanate.
[0045] In the present invention, unless otherwise specified, the curing accelerator used in the embodiments of the present invention is an organic tin accelerator purchased from Evonik, model number T-120.
[0046] Example 1
[0047] Reference Figure 1 As shown, the insulating adhesive film for busbars of this embodiment includes an insulating film layer 1 and an adhesive layer 2 arranged on the insulating film layer 1; wherein the insulating film layer 1 is a polyethylene terephthalate film layer with a thickness of 125 μm; the thickness of the adhesive layer 2 is 30 μm; and the adhesive layer 2 is prepared by an adhesive;
[0048] The raw material components of the adhesive and their weight parts are as follows: 80 parts of saturated polyester resin, 20 parts of tackifying resin, 40 parts of flame retardant filler, 2 parts of room temperature reactive curing agent, 5 parts of blocked isocyanate, 0.1 parts of curing accelerator, and 150 parts of organic solvent;
[0049] The saturated polyester resin is ES380 from SK Chemical, with a number average molecular weight of about 18,000, a glass transition temperature of 27°C, a hydroxyl value of 11 mgKOH / g, and an acid value of 0.1 mgKOH / g;
[0050] The tackifying resin is NPES901 from Nan Ya Plastics, with a softening point of 64°C-74°C;
[0051] The flame retardant filler is diethyl aluminum hypophosphite;
[0052] The room temperature reactive curing agent is hexamethylene diisocyanate trimer;
[0053] The blocked isocyanate is 3,5-dimethylpyrazole blocked hexamethylene diisocyanate trimer, and the deblocking temperature is 100℃-110℃;
[0054] The organic solvent is butanone;
[0055] The preparation of the adhesive specifically includes the following steps: uniformly dispersing saturated polyester resin, tackifying resin, flame retardant filler, curing agent and curing accelerator in an organic solvent to obtain the adhesive.
[0056] Example 2
[0057] The insulating adhesive film for busbars of this embodiment includes an insulating film layer 1 and an adhesive layer 2 disposed on the insulating film layer 1; wherein the insulating film layer 1 is a polyimide film layer with a thickness of 100 μm; the adhesive layer 2 has a thickness of 20 μm; and the adhesive layer 2 is prepared by an adhesive;
[0058] The raw material components of the adhesive and their weight parts are as follows: 75 parts of saturated polyester resin, 25 parts of tackifying resin, 40 parts of flame retardant filler, 1.5 parts of room temperature reactive curing agent, 4.5 parts of blocked isocyanate, 0.1 parts of curing accelerator, and 150 parts of organic solvent;
[0059] The saturated polyester resin is ES380 from SK Chemical, with a number average molecular weight of about 18,000, a glass transition temperature of 27°C, a hydroxyl value of 11 mgKOH / g, and an acid value of 0.1 mgKOH / g;
[0060] The tackifying resin is GA90A from Arakawa Chemical, with a softening point of 88°C-93°C;
[0061] The flame retardant filler is diethyl aluminum hypophosphite;
[0062] The room temperature reactive curing agent is hexamethylene diisocyanate trimer;
[0063] The blocked isocyanate is 3,5-dimethylpyrazole blocked hexamethylene diisocyanate trimer, and the deblocking temperature is 100℃-110℃;
[0064] The organic solvent is butanone;
[0065] The preparation of the adhesive specifically includes the following steps: uniformly dispersing saturated polyester resin, tackifying resin, flame retardant filler, curing agent and curing accelerator in an organic solvent to obtain the adhesive.
[0066] Example 3
[0067] The busbar insulating film of this embodiment includes an insulating film layer 1 and an adhesive layer 2 disposed on the insulating film layer 1; wherein the insulating film layer 1 is a polyethylene naphthalate film layer with a thickness of 100 μm; the adhesive layer 2 has a thickness of 20 μm; and the adhesive layer 2 is prepared from an adhesive;
[0068] The raw material components of the adhesive and their weight parts are as follows: 75 parts of saturated polyester resin, 25 parts of tackifying resin, 40 parts of flame retardant filler, 1.5 parts of room temperature reactive curing agent, 4.5 parts of blocked isocyanate, 0.1 parts of curing accelerator, and 150 parts of organic solvent;
[0069] The saturated polyester resin is ES403 from SK Chemical, with a number average molecular weight of about 9000, a glass transition temperature of 40°C, a hydroxyl value of 9 mgKOH / g, and an acid value of less than 3 mgKOH / g;
[0070] The tackifying resin is SH2095 from Jinan Shengquan, with a softening point of 92°C-98°C;
[0071] The flame retardant filler is melamine;
[0072] The room temperature reactive curing agent is isophorone diisocyanate trimer;
[0073] The blocked isocyanate is 2-methylimidazole blocked isophorone diisocyanate trimer, and the deblocking temperature is 110℃-120℃;
[0074] The organic solvent is butanone;
[0075] The preparation of the adhesive specifically includes the following steps: uniformly dispersing saturated polyester resin, tackifying resin, flame retardant filler, curing agent and curing accelerator in an organic solvent to obtain the adhesive.
[0076] Example 4
[0077] The busbar insulating adhesive film of this embodiment includes an insulating film layer 1 and an adhesive layer 2 disposed on the insulating film layer 1; wherein the insulating film layer 1 is a polyphenylene ether film layer with a thickness of 175 μm; the adhesive layer 2 has a thickness of 30 μm; and the adhesive layer 2 is prepared by an adhesive;
[0078] The raw material components of the adhesive and their weight parts are as follows: 70 parts of saturated polyester resin, 30 parts of tackifying resin, 30 parts of flame retardant filler, 2 parts of room temperature reactive curing agent, 6 parts of blocked isocyanate, 0.1 parts of curing accelerator, and 140 parts of organic solvent;
[0079] The saturated polyester resin is Vylon226 produced by Toyobo, with a number average molecular weight of about 8000, a glass transition temperature of 65°C, a hydroxyl value of 20 mgKOH / g, and an acid value of less than 2 mgKOH / g;
[0080] The tackifying resin is NPES904 from Nan Ya Plastics, with a softening point of 96°C-107°C;
[0081] The flame retardant filler is diethyl aluminum hypophosphite;
[0082] The room temperature reactive curing agent is hexamethylene diisocyanate trimer;
[0083] The blocked isocyanate is methyl tert-butyl ketone oxime blocked hexamethylene diisocyanate trimer, and the deblocking temperature is 100℃-120℃;
[0084] The organic solvent is butanone;
[0085] The preparation of the adhesive specifically includes the following steps: uniformly dispersing saturated polyester resin, tackifying resin, flame retardant filler, curing agent and curing accelerator in an organic solvent to obtain the adhesive.
[0086] Example 5
[0087] The busbar insulating adhesive film of this embodiment includes an insulating film layer 1 and an adhesive layer 2 disposed on the insulating film layer 1; wherein the insulating film layer 1 is a polyphenylene ether film layer with a thickness of 250 μm; the adhesive layer 2 has a thickness of 35 μm; and the adhesive layer 2 is prepared from an adhesive;
[0088] The raw material components of the adhesive and their weight parts are as follows: 80 parts of saturated polyester resin, 20 parts of tackifying resin, 45 parts of flame retardant filler, 2.5 parts of room temperature reactive curing agent, 6.5 parts of blocked isocyanate, 0.1 parts of curing accelerator, and 155 parts of organic solvent;
[0089] The saturated polyester resin is ES380 from SK Chemical, with a number average molecular weight of about 18,000, a glass transition temperature of 27°C, a hydroxyl value of 11 mgKOH / g, and an acid value of 0.1 mgKOH / g;
[0090] The tackifying resin is SH2116 from Jinan Shengquan, with a softening point of 110℃-118℃;
[0091] The flame retardant filler is aluminum hydroxide;
[0092] The room temperature reactive curing agent is diphenylmethane diisocyanate trimer;
[0093] The blocked isocyanate is diisopropyl ketoxime blocked diphenylmethane diisocyanate trimer, and the deblocking temperature is 100℃-110℃;
[0094] The organic solvent is butanone;
[0095] The preparation of the adhesive specifically includes the following steps: uniformly dispersing saturated polyester resin, tackifying resin, flame retardant filler, curing agent and curing accelerator in an organic solvent to obtain the adhesive.
[0096] Comparative Example 1
[0097] The method is basically the same as Example 1, except that the amount of saturated polyester resin is replaced by 95 parts, and the amount of tackifying resin is replaced by 5 parts.
[0098] Comparative Example 2
[0099] The method is basically the same as Example 1, except that the tackifying resin is replaced with Nan Ya Plastics NPES909, which has a softening point of 130°C-150°C.
[0100] Comparative Example 3
[0101] The method is basically the same as Example 1, except that the amount of the room temperature reactive curing agent is replaced by 0.4 parts, and the amount of the blocked isocyanate is replaced by 1 part.
[0102] Comparative Example 4
[0103] The method is basically the same as Example 1, except that the amount of the room temperature reactive curing agent is replaced by 5 parts, and the amount of the blocked isocyanate is replaced by 2 parts.
[0104] Comparative Example 5
[0105] The method is basically the same as Example 1, except that the blocked isocyanate is replaced by phenol-blocked hexamethylene diisocyanate trimer, and the deblocking temperature is 130° C.-150° C.
[0106] Performance Testing
[0107] The busbar insulating films of Examples 1-5 and Comparative Examples 1-5 were tested, and the test methods of the test items were as follows:
[0108] (1) Low-temperature rapid hot pressing process bonding effect: The busbar insulation film and the tinned copper busbar are pressed together under different conditions. If there are no bubbles or debonding, and the residual glue is uniform after peeling, it is qualified, otherwise it is unqualified;
[0109] (2) Bonding strength: The bonding strength between the busbar insulating film and the tinned copper busbar, 90° peel test;
[0110] (3) High temperature and high humidity aging performance: After the busbar insulation film and tinned copper busbar are hot pressed, a high temperature and high humidity aging test is carried out. The test conditions are: 85°C / 85%RH / 1000h;
[0111] (4) Thermal shock aging performance: After the busbar insulation film and tinned copper busbar were hot pressed, a thermal shock aging test was performed. The test conditions were: -40°C to 125°C / 500 cycles, -40°C constant temperature for 1 hour, 125°C constant temperature for 1 hour, temperature switching time was less than 3 minutes, and one cycle was about 2 hours;
[0112] (5) Thermal oxidative aging performance: After the busbar is hot-pressed with an insulating adhesive film and a tinned copper busbar, a thermal oxidative aging test is performed. The test conditions are: baking at 130°C for 1000 hours.
[0113] Table 1 shows the relevant properties of the busbar insulation film finally measured:
[0114] Table 1
[0115]
[0116] It can be seen from Table 1 that the bonding strength of the busbar insulating adhesive film of Examples 1-5 is 1.66N / mm-2.93N / mm, the low-temperature rapid hot pressing process bonding effect is qualified, and the high-temperature and high-humidity, cold and hot shock and thermal oxygen aging performance are qualified.
[0117] Compared with Example 1, the amount of saturated polyester resin added in Comparative Example 1 is too much, and the amount of tackifying resin added is too little, resulting in poor fluidity of the adhesive layer of the prepared busbar insulating film, and unsatisfactory short-time hot pressing bonding effect;
[0118] Compared with Example 1, the softening point of the tackifying resin in Comparative Example 2 is too high, resulting in poor fluidity of the adhesive layer of the prepared busbar insulating film, and unsatisfactory hot pressing bonding effect in a short time;
[0119] Compared with Example 1, the amount of curing agent added in Comparative Example 3 is too small, resulting in a low degree of crosslinking of the adhesive layer of the prepared busbar insulating adhesive film, a low bonding strength, and unqualified high temperature and high humidity resistance and thermal oxygen aging resistance;
[0120] Compared with Example 1, the proportion of room temperature reactive curing agent added in Comparative Example 4 is too high, resulting in a high degree of crosslinking of the adhesive layer of the prepared busbar insulating adhesive film, poor fluidity, and unsatisfactory short-time hot pressing bonding effect;
[0121] Compared with Example 1, the desealing temperature of the curing agent in Comparative Example 5 is too high, resulting in less curing agent release during hot pressing of the manufactured busbar insulating adhesive film, lower bonding strength, and unqualified high temperature and high humidity resistance.
[0122] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. An adhesive, characterized in that: The adhesive comprises, by weight, 40-90 parts of a saturated polyester resin, 10-40 parts of a tackifying resin, 30-80 parts of a flame retardant filler, 3-10 parts of a curing agent, 0.1-0.5 parts of a curing accelerator and 50-300 parts of an organic solvent; the tackifying resin has a softening point of 40° C.-120° C.; the curing agent comprises a reactive isocyanate and a blocked isocyanate; the unblocking temperature of the blocked isocyanate is 70° C.-120° C.; and the mass ratio of the reactive isocyanate to the blocked isocyanate is 1:(1-5).
2. The adhesive according to claim 1, characterized in that: The reactive isocyanate is selected from one or more of diisocyanate and its dimer, trimer and biuret polyisocyanate.
3. The adhesive according to claim 1, characterized in that: The blocked isocyanate is obtained by reacting a blocking agent with the reactive isocyanate according to claim 2; the molar ratio of active hydrogen in the blocking agent to isocyanate in the reactive isocyanate is (1-1.5):
1.
4. The adhesive according to claim 3, characterized in that: The blocking agent is selected from one or more of methyl tert-butyl ketone oxime, diisopropyl ketone oxime, 3,5-dimethylpyrazole, 2-methylimidazole and 1,2,4-triazole; The reaction temperature is 20°C-100°C, and the reaction time is 0.5h-6h.
5. The adhesive according to claim 1, characterized in that: The saturated polyester resin has a number average molecular weight of 3000-40000, a glass transition temperature of -20°C to 80°C, a hydroxyl value of 8mgKOH / g-20mgKOH / g, and an acid value of no more than 3mgKOH / g.
6. The adhesive according to claim 1, characterized in that: The tackifying resin is selected from one or more of rosin resin, epoxy resin, terpene resin, phenolic resin and petroleum resin; The flame retardant filler is selected from one or more of phosphorus flame retardants, nitrogen flame retardants and metal hydroxides; The curing accelerator is selected from organotin accelerators; The organic solvent is selected from one or more of butanone, acetone, cyclohexanone, ethyl acetate and butyl acetate.
7. The method for preparing the adhesive according to any one of claims 1 to 6, characterized in that: The following steps are involved: The saturated polyester resin, tackifying resin, flame retardant filler, curing agent and curing accelerator are uniformly dispersed in an organic solvent to obtain the adhesive.
8. An insulating film for a busbar, characterized in that: The insulating adhesive film for the busbar comprises an insulating film layer and an adhesive layer arranged on the insulating film layer; the adhesive layer is prepared by the adhesive according to any one of claims 1-6.
9. The insulating adhesive film for busbar according to claim 8, characterized in that: The insulating film layer is selected from a polyethylene terephthalate film layer, a polybutylene terephthalate film layer, a polyethylene naphthalate film layer, a polyimide film layer, a polycarbonate film layer, an aromatic polyamide film layer, a polyphenylene sulfide film layer or a polyphenylene ether film layer.
10. The insulating adhesive film for busbar according to claim 8, characterized in that: The thickness of the insulating film layer is 50 μm-300 μm; the thickness of the adhesive layer is 10 μm-50 μm.
Citation Information
Patent Citations
Insulating adhesive film for laminated bus bar and laminated bus bar
CN104178044A
Thermoplastic resin composition and adhesive prepared from composition, insulation adhesive film for laminated bus bars, and preparation method of insulation adhesive film
CN106675003A
Halogen-free thermoplastic resin composition, prepared adhesive prepared by adopting compositon, insulating adhesive film for laminated busbar and preparation method of insulating adhesive film
CN106700509A